Thermal Management Technologies for Improving the Thermal Stability of Perovskite Solar Cells - Wan, Zhongquan; Wei, Runmin; Zhao, Haibin; Yu, Wang; Azam, Muhammad; Luo, Junsheng; Jia, Chunyang (Nano-Micro Letters, 2026)
Perovskite solar cells (PSCs) have achieved excellent power conversion efficiencies; however, under direct sunlight, device temperatures can exceed ambient temperatures by more than 50 ℃, making thermal stability a critical challenge for commercialization. This review first summarizes the degradation mechanisms of PSCs induced by elevated temperatures, followed by a discussion of heat generation, with Joule heat identified as the primary contributor. Advanced thermal management strategies are then highlighted, including the use of high thermal conductivity materials, integration with thermoelectric devices, external radiative cooling layers, down-conversion approaches, and tandem structures. By systematically presenting these strategies, this review provides guidance for enhancing both the efficiency and thermal stability of PSCs, thereby supporting their pathway toward commercialization Highlights: 1 Joule heating is the dominant cause of elevated device temperature in perovskite solar cells (PSCs) under operation, significantly degrades their long-term thermal stability. 2 High temperatures degrade PSCs primarily through accelerated material decomposition and interfacial reactions, posing a major barrier to commercialization. 3 Key thermal management strategies, such as integrating thermally conductive materials, radiative cooling layers, and tandem structures, effectively suppress heat accumulation and enhance device durability.